2022
DOI: 10.21037/cdt-21-705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of coronary microvascular dysfunction in post-percutaneous coronary intervention patients with recurrent chest pain

Abstract: Background: Coronary microvascular dysfunction (CMD) and obstructive coronary artery disease (CAD) are likely to exist side-by-side, thereby probably inducing angina pectoris symptoms of some patients not effectively relieved after revascularization. We aimed to evaluate the prevalence and characteristics exhibited by CMD in patients with recurrent chest pain who received percutaneous coronary intervention (PCI) before. Methods:We conducted a single-center cross-sectional retrospective study. A total of 373… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although the relationship between the increase in BMI and CMD is not well-established, BMI is directly proportional to blood levels of lipids, glucose, and inflammatory factors. Indeed, our previous study showed that BMI is an independent predictor of CMD in obstructive coronary artery disease ( 27 ). Previous studies using PET have shown that MFR is reduced in patients with normal CAG and asymptomatic hypercholesterolemia ( 28 ), but can be reversed by lipid-lowering medications ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between the increase in BMI and CMD is not well-established, BMI is directly proportional to blood levels of lipids, glucose, and inflammatory factors. Indeed, our previous study showed that BMI is an independent predictor of CMD in obstructive coronary artery disease ( 27 ). Previous studies using PET have shown that MFR is reduced in patients with normal CAG and asymptomatic hypercholesterolemia ( 28 ), but can be reversed by lipid-lowering medications ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we focused on the role of CMD because it has a central role in the complex pathophysiology of MINOCA and INOCA. The assessment of coronary microcirculation may be performed invasively and non-invasively, and it should be implemented both in MINOCA/INOCA and in myocardial ischemia due to atherosclerotic disease, also because of the main pathophysiological role of CMD in patients undergoing percutaneous coronary interventions [112,113]. CMD consists of structural and functional alterations of microcirculation, which hamper the cross-talk between coronary circulation and myocardial metabolism.…”
Section: Discussionmentioning
confidence: 99%